2017
DOI: 10.1038/s41598-017-04545-4
|View full text |Cite
|
Sign up to set email alerts
|

New insights on the complex dynamics of two-phase flow in porous media under intermediate-wet conditions

Abstract: Multiphase flow in porous media is important in a number of environmental and industrial applications such as soil remediation, CO2 sequestration, and enhanced oil recovery. Wetting properties control flow of immiscible fluids in porous media and fluids distribution in the pore space. In contrast to the strong and weak wet conditions, pore-scale physics of immiscible displacement under intermediate-wet conditions is less understood. This study reports the results of a series of two-dimensional high-resolution … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
55
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 92 publications
(60 citation statements)
references
References 36 publications
2
55
0
Order By: Relevance
“…1(c-d) indicates the pressure values normalized with respect to the outlet pressure. The direction of injection in all images is from bottom to top (Rabbani et al, 2017). oil/gas recovery.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…1(c-d) indicates the pressure values normalized with respect to the outlet pressure. The direction of injection in all images is from bottom to top (Rabbani et al, 2017). oil/gas recovery.…”
Section: Discussionmentioning
confidence: 99%
“…Intermediate-wet conditions prevail extensively in many natural formations (Alyafei and Blunt, 2016), and only a few studies have focused on this issue (Iglauer et al, 2016). For instance, the co-existence of concave and convex interfaces occurring in intermediate-wet rock was demonstrated by using a 2D VOF simulation (Rabbani et al, 2017), which emanate from the interplay between the wetting characteristics and pore geometry (as illustrated in Fig. 3a).…”
Section: Local Interfacial Instabilities Under Intermediate-wet Condimentioning
confidence: 99%
See 1 more Smart Citation
“…Several mechanisms are proposed to explain the incremental oil recovery associated with MEOR, among which are the reduction in the oil-water IFT and changes in the wettability of the system and selective plugging mechanism [10][11][12][13]. Numerous experimental and numerical studies have been conducted to understand the impact of wettability alteration and IFT reduction [14][15][16][17][18][19][20][21][22][23][24]. Kowalewski et al [25] showed that the bacterial growth could both reduce IFT and alter the wettability state toward less oil-wet conditions.…”
Section: Introductionmentioning
confidence: 99%
“…In the past few years, increasing attention has been focused on the effects of disordered geometry on immiscible two-phase flow (Ferrari et al, 2015;Holtzman, 2016;Rabbani et al, 2017). The ordered and disordered porous media have clear differences in the behaviours and mechanisms of multiphase fluid displacement processes (Pak et al, 2015).…”
Section: Introductionmentioning
confidence: 99%